2021
DOI: 10.1038/s41598-021-83873-y
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in brains of patients with disorders of consciousness treated with deep brain stimulation

Abstract: Disorders of consciousness (DOC) are one of the major consequences after anoxic or traumatic brain injury. So far, several studies have described the regaining of consciousness in DOC patients using deep brain stimulation (DBS). However, these studies often lack detailed data on the structural and functional cerebral changes after such treatment. The aim of this study was to conduct a volumetric analysis of specific cortical and subcortical structures to determine the impact of DBS after functional recovery of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Some researchers have explored the possibility of using deep brain stimulation (DBS), a technique that delivers electrical impulses to specific brain areas, to treat disorders of consciousness (DoC), which are conditions that affect the level or content of consciousness in patients who have suffered a severe brain injury. One study reported that DBS increased the volume of the caudate nucleus in DoC patients (Raguz et al, 2021 ). However, it is controversial whether such structural changes are the result of deep brain stimulation effects or caused by recovery of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have explored the possibility of using deep brain stimulation (DBS), a technique that delivers electrical impulses to specific brain areas, to treat disorders of consciousness (DoC), which are conditions that affect the level or content of consciousness in patients who have suffered a severe brain injury. One study reported that DBS increased the volume of the caudate nucleus in DoC patients (Raguz et al, 2021 ). However, it is controversial whether such structural changes are the result of deep brain stimulation effects or caused by recovery of consciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the insula does not have to be specifically targeted with stimulation in order to restore in function. For example, deep brain stimulation (DBS) of the ventral anterior limb of the internal capsule showed to restore insular function in patients with an obsessive compulsive disorder 68 while DBS of the thalamus showed to increase volume of several brain regions, including the insula, in patients with disorders of consciousness 69 . Altogether there is promising evidence that either direct or indirect stimulation of the insula could be effective in the treatment of substance use disorder 32,66 Although speculative, the findings of the current study suggest that insular stimulation may be particularly effective in the treatment of women.…”
Section: Discussionmentioning
confidence: 99%
“… 147 It remains a question whether DBS in these patients, as well as performing the procedure relatively early after injury, can induce return of residual brain functions and/or prevent secondary complications after brain injury. 144 , 148 …”
Section: The Intralaminar Thalamus As Target For Restoring Consciousn...mentioning
confidence: 99%